Church and culture: A religio-theological perspective - Merwe, P. J. van der (HTS teologiese studies, 2005)
The ethnic church (“volkskerk”) is central to the ecclesiology and Church Order of the Reformed Church in Africa (Nederduitsch Hervormde Kerk). This article questions notions of culture, ethnicity, ethnic people (“volk”) and ethnic identity as backdrop for answering the question on the responsibility of the church towards cultural and ethnic identity. It is conceded that civil religion remains an insidious threat to the church, as is also civil ideology. Lastly, it is contended that the main responsibility of the church towards culture, ethnic people, ethnic and social identity is one of apostolic prophetic presence and outreach.